PENGARUH RASIO PROFITABILITAS DAN RASIO NILAI PASAR TERHADAP RETURN SAHAM - Sutomo, Lilik; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to disclose how the influence of ratios i.e.: profitability (ROE) and market value ratio (PER and EPS) both partial and simultaneous to the stock return on food and beverages companies which are listed in the IDX in 2012-2015 periods. The population is allfood and beveragessector manufacturing companiesin 2012-2015 periods. The samples are 9 food and beverages sectormanufacturing companies and they still exist in the perception periods and they havebeen published in 2012-2015 and selected by using purposive sampling. The analysis method has been done by using multiple regression analysis to obtain comprehensive descriptionaboutthe correlationamong variables. The result of the t-test shows that only the ROE which does not give significant influence to the stock return whereas the PER and the EPS give significant influence to the stock returns. In addition,it has been found from the result of the F-test indicates that ROE, PER and EPS simultaneously giveinfluence to thestock return.Keywords: Return of equity (ROE), price earning ratio (PER), earning per share (EPS), stock return.